Foot and Mouth Disease Outbreak in Indonesia: Summary and Implications - Rosalie Chen; Evangeline Gardiner; Ashley Quigley (Global Biosecurity, 2022)
This Watching Brief details a foot-and-mouth disease (FMD) outbreak in livestock in Indonesia. The outbreak, first reported in May 2022, is causing significant socioeconomic, animal health and biosecurity concerns in a country that has been FMD-free without vaccination since 1986. Delayed index case notification, difficulties with vaccination (e.g. accessibility issues, waning vaccine immunity and lack of cross-protection), limited understanding of persistent infection in carrier animals and lengthy restocking processes all present challenges for Indonesia in containing and recovering from this FMD outbreak. Thus, despite extensive research, the disease continues to present substantial challenges for outbreak prevention, surveillance and containment, which have important implications considering the widespread global prevalence of FMD and its impact on agriculture and trade in many countries. The socioeconomic burden of the current outbreak in Indonesia on individuals, households and communities is devastating, particularly in poor and rural areas. These impacts will likely continue after the outbreak is over, highlighting the need for co-ordinated support in strengthening outbreak detection and control in FMD-affected and other vulnerable areas.